2010
DOI: 10.1177/0022034510363662
|View full text |Cite
|
Sign up to set email alerts
|

In vitro Remineralization of Severely Compromised Bonded Dentin

Abstract: Biomimetic remineralization is potentially useful for remineralizing incompletely resin-infiltrated collagen matrices created by etch-and-rinse adhesives. In this study, we tested the hypothesis that structurally-altered dentin collagen cannot be remineralized to the same hierarchical order and dimension that are seen in structurally-intact dentin collagen The remineralization medium consisted of a set Portland cement/simulated body fluid system containing polycarboxylic acid and polyvinylphosphonic acid as bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 34 publications
(44 reference statements)
2
32
0
Order By: Relevance
“…Moreover, degradation of the demineralized collagen matrices from the surface of the remineralized artificial caries-like lesions by endogenous matrix metalloproteinases present in dentin [28] was not observed in the present study as a result of the improved remineralization kinetics. This phenomenon has previously been observed using the proof-on-concept biomimetic remineralization strategy [47] and mimics the tubular occlusion observed in carious dentin [48]. As the experimental protocol involved placement of set MTA over the dentin lesion, such a phenomenon could not have been caused by introduction of fine MTA particles into the dentinal tubules and represented genuine intratubular apatite deposits.…”
Section: Discussionsupporting
confidence: 59%
“…Moreover, degradation of the demineralized collagen matrices from the surface of the remineralized artificial caries-like lesions by endogenous matrix metalloproteinases present in dentin [28] was not observed in the present study as a result of the improved remineralization kinetics. This phenomenon has previously been observed using the proof-on-concept biomimetic remineralization strategy [47] and mimics the tubular occlusion observed in carious dentin [48]. As the experimental protocol involved placement of set MTA over the dentin lesion, such a phenomenon could not have been caused by introduction of fine MTA particles into the dentinal tubules and represented genuine intratubular apatite deposits.…”
Section: Discussionsupporting
confidence: 59%
“…Prior to this report (Atmeh et al) [6], a similar hypermineralised layer was observed on the of the resin-dentine interface (i.e. hybrid layer) when set white Portland cement was used to remineralise hybrid layers created in severely compromised bonded dentine [102]. Whilst this 'mineral infiltration zone' enables a calcium silicate cement to 'bond' to dentine, it is likely to be highly brittle because type I collagen, which is responsible for the toughness of biological mineralised tissues [8,94], is destroyed by the alkalinity of the calcium silicate cements.…”
Section: Indirect Evidence Of In Vitro Bioactivitymentioning
confidence: 59%
“…In this interaction, the highly caustic (alkaline) calcium silicate cement hydration products are responsible for the degradation of the collagenous component of intertubular dentine. A porous intertubular dentine layer is produced in which the collagen fibrils are depleted, leaving behind porous 'mineral ghosts' [102] that enable the permeation of high concentrations of calcium, hydroxyl and carbonate ions to form a hypermineralised layer [6]. Such a process has been termed 'alkaline etching' [6], to distinguish it from the 'acid etching' process associated with the use of dentine adhesives and glass ionomer cements.…”
Section: Indirect Evidence Of In Vitro Bioactivitymentioning
confidence: 99%
“…This strategy reproduced both intrafibrillar and interfibrillar minerals and recapitulated the dimension and order of the apatite crystallites that are found in natural dentin [70][71][72][73]. Using this biomimetic remineralization strategy, both hybrid layers created by etch-and-rinse adhesives [68,74,75] and moderately aggressive self-etch adhesives [65,74,76], as well as 250-to 300-μm-thick completely demineralized dentin lesions, can be remineralized [77][78][79]. This bottom-up remineralization strategy does not rely on seed crystallites, and may be considered as a potentially useful mechanism in extending the longevity of resin-dentin bonds [80] via restoring the dynamic mechanical properties of the denuded collagen within the hybrid layer to approximate those of mineralized dentin [81].…”
Section: Fluoride-free Adhesivesmentioning
confidence: 81%